2005
DOI: 10.1177/082585970502100310
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Psychosocial and Physical Functioning in Patients with Motor Neurone Disease and Metastatic Cancer

Abstract: Although their disease processes and treatments are different, patients with motor neurone disease (MND) and those with late-stage cancer share a common situation—one in which the quality of life, rather than a cure, becomes the focus of care. We report here a comparison of 126 patients with MND and 125 with metastatic cancer on a range of physical and psychosocial measures. Compared to cancer patients, MND patients were younger, had greater social contacts, but were more physically impaired. Cancer patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 41 publications
(36 reference statements)
2
29
0
Order By: Relevance
“…Depression was assessed with the Depression, Anxiety and Stress Scales 21 (DASS‐21) , a self‐report measure with 21 items, each rated from 0 (did not apply to me at all) to 3 (applied to me very much or most of the time). To accurately evaluate the relationship between apathy and symptoms of depression, each item on the depression subscale was categorized into specific symptom clusters of depression referred to as depression with demoralization (sum of DASS‐21 items 10, 13, 17 and 21 ≥1 indicated the presence of symptoms) or depression with anhedonia (sum of DASS‐21 items 3, 5 and 16 ≥1 indicated the presence of symptoms) according to a previous ALS study (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Depression was assessed with the Depression, Anxiety and Stress Scales 21 (DASS‐21) , a self‐report measure with 21 items, each rated from 0 (did not apply to me at all) to 3 (applied to me very much or most of the time). To accurately evaluate the relationship between apathy and symptoms of depression, each item on the depression subscale was categorized into specific symptom clusters of depression referred to as depression with demoralization (sum of DASS‐21 items 10, 13, 17 and 21 ≥1 indicated the presence of symptoms) or depression with anhedonia (sum of DASS‐21 items 3, 5 and 16 ≥1 indicated the presence of symptoms) according to a previous ALS study (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…This will be assessed utilizing the Herth Hope Index [21,22], a validated instrument developed for use with the terminally ill. Distressed MND patients score higher on hopelessness than distressed cancer patients at the end of life [23], and interest in hastened death or suicidal ideation in the MND population has been shown to correlate with hopelessness [3,24], which indicates that the level of hopefulness a key factor of psychological distress in this disease population.…”
Section: Methodsmentioning
confidence: 99%
“…8 Previous research has shown that patients with MND experience significantly more negative emotions, particularly hopelessness and helplessness, than patients with cancer. 9 A comprehensive review of the literature revealed that the experience of diagnosis, assisted ventilation, cognitive changes, and end-of-life decision-making create challenges within a short time for MND caregivers, underscoring the need for supportive interventions. 3 People with MND and their families often describe their care experiences as unrelenting and worse than cancer because of the progressive nature of the disease and the hopelessness of recovery.…”
Section: Introductionmentioning
confidence: 99%